Modelling of Arterial Bifurcation by Means of Electromechanical Model with Distributed Parameters - Czippelova, Barbora; Gombarska, Daniela (Communications - Scientific Letters of the University of Zilina, 2011)
The present paper deals with the computer-aided modelling of blood vessels bifurcations using the electro-mechanical analogy with the electric transmission lines. The present model allows assessing the Murray's cubic law and its comparison with the real state of large and small arteries branching in the human body.
Keywords: no keywords